2014
DOI: 10.4108/sg.1.3.e4
|View full text |Cite
|
Sign up to set email alerts
|

Deploying Serious Games for Management in Higher Education: lessons learned and good practices

Abstract: Deployment of serious games (SGs) and their insertion in higher education (HE) curricula is still low. The literature lacks papers describing deployment of SGs in HE critically showing educational benefits and providing guidelinesand good practices for their use. With the present work, we intend to make a first step in this direction, by reporting our experience in using state of the art managerial SGs in MSc engineering/business courses in four different European universities. In order to describe and analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Although all of the studies in our dataset somehow focus on learning objectives and simulations or games, only 29 reviewed articles explicitly refer to learning theories as conceptualized, for instance, by Bloom [1] or Romiszowski [7]. However, in labeling the declared learning goals in the articles, we found that simulations and games are deployed to develop a diverse range of cognitive and communicative skills: 37% related the simulation or game to productive cognitive skills (for example [27], [29], [30], [31]), 16% procedural knowledge (for instance, [28], [32], [33], [34]), and 12% productive interactive skills (such as [27], [30], [34]). Important to note is that most studies mentioned several learning objectives relevant to their research.…”
Section: Tentative Positive Effect On Learning Objectivesmentioning
confidence: 93%
See 2 more Smart Citations
“…Although all of the studies in our dataset somehow focus on learning objectives and simulations or games, only 29 reviewed articles explicitly refer to learning theories as conceptualized, for instance, by Bloom [1] or Romiszowski [7]. However, in labeling the declared learning goals in the articles, we found that simulations and games are deployed to develop a diverse range of cognitive and communicative skills: 37% related the simulation or game to productive cognitive skills (for example [27], [29], [30], [31]), 16% procedural knowledge (for instance, [28], [32], [33], [34]), and 12% productive interactive skills (such as [27], [30], [34]). Important to note is that most studies mentioned several learning objectives relevant to their research.…”
Section: Tentative Positive Effect On Learning Objectivesmentioning
confidence: 93%
“…Thirteen studies claimed the role of the instructor is vital for achieving learning objectives through simulations and games [26], [28], [29], [30], [31], [32], [33], [35], [36], [37], [38], [39], [40]. Baalsrud Hauge et al [33] show that the role of the teachers becomes more important when the emphasis on abstraction increases. In their meta-analysis, Wouters & Van Oostendorp [41] identify that the role of instructional support enhances learning, especially when learning objectives involve (higher order) skills, and in discussing and selecting new information.…”
Section: Enabling and Constraining Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a key to a successful implementation of shared resources concept in supply chains is to increase the awareness [18]. Due to its high motivation factor and the possibility to let the participants play an active role, the use of experiential learning forms has been increasing within education at all levels [19,20,21]. With SCM and OR education, serious games are regularly used to overcome the gap between theory and practices.…”
Section: Why Use Serious Gamesmentioning
confidence: 99%
“…Based on this information, the next step would be to identify to what extent a game can be reengineered and which of the gaming features need to be changed/ adapted/ repurposed [16]. Typical criteria for selection include various factors such as: coverage of the needed educational topics; matching between the course's learning objectives and the game's features; costs; usability; quality of user assessment and provision of feedback; degree of freedom for players and teachers; the game's learning curve, difficulty level and long-term playability; competences and effort needed on the teacher's side; relation of game and learning mechanics [13,15,17].…”
Section: Introductionmentioning
confidence: 99%